Caesarean scar ectopic pregnancy of 12 weeks: a rare and unexpected long-term complication of caesarean section - Agrawal, Priti; Agrawal, Rishi; Agrawal, Sujeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Caesarean scar ectopic pregnancy (CSEP) is one of the rarest of all ectopic pregnancies. CSEP is a life-threatening condition and should be timely diagnosed and managed because if left untreated, it may lead to serious complications like uterine rupture, hemorrhage, hypovolemic shock and even maternal death. A 29-year-old female with history of amenorrhea 3 months, was referred from remote rural area with severe abdominal pain and vaginal bleeding for 15 days. Her previous childbirth was by caesarean section (CS), 4 years back. Trans abdominal ultrasonography (USG) revealed gestational sac in lower uterine segment and attached to anterior wall. Upper uterine segment was empty, crown lump length was 5.86 cm corresponding to 12 weeks and 3 days. As the pregnancy was 12 weeks with very thin myometrium covering it and placenta fully covering internal orifice of the cervix uteri (internal OS), took decision for laparotomy. Vaginal bleeding and abdominal pain are the most common presenting symptoms of CSEP. Severe acute abdominal pain or heavy vaginal bleeding may indicate impending rupture while hemodynamic instability may indicate rupture of CSEP. Laparoscopy or laparotomy can be done in such cases to remove pregnancy. Chose laparotomy as it would give quick, better access and control of hemorrhage in this case. The risk of CSEP and placenta accrete should be specially emphasized when counselling women requesting CS for nonmedical reasons. Prompt and accurate diagnosis using transvaginal ultrasonography (TVUS) followed by individualized treatment will significantly help to reduce morbidity related to CSEP.